Judicial Activism: The Indian Experience - S. P. Sathe (Washington University Journal of Law & Policy, 2001)
Judicial activism has become a subject of controversy in India. Recent and past attempts to hinder the power of the courts, as well as access to the courts, included indirect methods of disciplining the judiciary, such as supersession of the judges and transfers of inconvenient judges. Critics of judicial activism say that the courts usurp functions allotted to the other organs of government. On the other hand, defenders of judicial activism assert that the courts merely perform their legitimate function. According to Mr. Justice A. H. Ahmadi, the former Chief Justice of India, judicial activism is a necessary adjunct of the judicial function because the protection of public interest, as opposed to private interest, is the main concern.
Keywords: Judicial activism; Political questions & amp; judicial power – India; Constitutional law – India; India. Supreme Court